Urgency of Regulatory Updates in Law Enforcement Against Fraudulent Acts by Health Facilities in the National Health Insurance Program - Fani, Veranika Santiani; Suparno, Suparno (International Journal of Social Service and Research, 2025)
The National Health Insurance (JKN) Program in Indonesia faces significant challenges in law enforcement against fraudulent activities by health facilities. Despite the implementation of Minister of Health Regulation No. 16 of 2019, which addresses fraud through administrative sanctions, the regulation has shown limitations, particularly the absence of criminal sanctions. This study utilizes a normative juridical method with a statutory approach and descriptive-analytical specifications to evaluate the current regulatory framework and the need for stronger legal measures. The analysis reveals that the current sanctions, limited to warnings and fines, lack a deterrent effect, enabling repeated fraudulent practices that undermine the JKN system. This paper suggests the introduction of criminal sanctions, which would align the regulation with the broader legal framework, including the Criminal Code and anti-corruption laws. The implications of this regulatory gap are significant, as it hampers the effectiveness of law enforcement, impacts public trust in the system, and threatens the sustainability of health services. Strengthening the regulation will improve accountability, ensure transparency, and protect citizens' rights to health services, ultimately fostering a more robust and reliable national health insurance system.